Peran Keterampilan Berpikir Kritis Siswa di Sekolah Menengah Pertama pada Materi Sistem Pencernaan - Juniar Fauziatul Azizah; Muzzazinah Muzzazinah; Elfi Susanti (SAP (Susunan Artikel Pendidikan), 2021)
Critical thinking skills are higher order thinking skills that should be developed in schools, in line with the objectives of the 2013 revised curriculum which prioritizes 21st century skills as a provision for future life. This study aims to analyze and classify the level of students in constructing critical thinking skills. The research1subjects1were 28 students of class VIII B SMP Negeri 6 Ngawi for the academic year 2020/2021. Data collection was carried out through interviews and critical thinking skills tests. The method used was descriptive qualitative. The critical thinking skills test instrument was 5 essay questions consisting of 5 indicators. The results of the critical thinking skills test were declared valid in terms of the1results1of1validation, level of difficulty, differentiation, and reliability. The analysis was carried out on the student test results on each indicator and categorized into five critical thinking categories consisting of very good (VG), good (G), medium (M), low (L), and very low (VL). The results1showed that1the highest percentage of indicators of critical thinking was obtained by 32% which were indicators of tactical strategy setting. Critical thinking indicators obtained by the lowest percentage of 8% were indicators of building basic skills. This proves that critical thinking skills need to be further trained so that they can be improved in science learning and advance in the field of education.